Toxic effects of Karenia mikimotoi extracts on mammalian cells - 陈洋 颜天 于仁成 周名江 (Chinese journal of oceanology and limnology, 2011)
Karenia is one of the most harmful and representative red tide genus in a temperate zone. Blooms caused by this genus have resulted in massive fish death in the South China Sea and the East China Sea. However, the potential effects of this dinoflagellate on human health through the transfer of toxins via marine food webs, and the mechanisms of toxicity, are still unknown. Therefore, we examined the toxic effects of a strain of K. mikimotoi （isolated from the South China Sea） on the proliferation and morphology of four mammalian cell lines （two normal cell lines and two cancer cell lines）. In addition, we carried out a preliminary investigation on the mechanism of toxicity of the alga. The results show that the polar lipid-soluble component ofK. mikimotoi significantly inhibited proliferation of the four cell lines, and resulted in the ceils becoming spherical, swollen and damaged. The result of Annexin V and PI double-staining confirmed that cell membranes were disrupted. The malonaldehyde （MDA） contents in the medium of the four cell lines treated with the polar-lipid extracts all increased significantly, which indicates that the polar-lipid toxins produced by K. rnikimotoi could adversely affect mammalian cells by inducing lipid peroxidation. We conclude that K. mikimotoi is a potential threat to human health, and the comprehensive effect of this dinoflagellate and its mechanisms should be investigated further.